PSYCHOLOGICAL CHALLENGES IN HIGH-FREQUENCY TRADING: STRESS, DECISION-MAKING, AND RISK MANAGEMENT (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
High-frequency trading (HFT) exposes traders to intense psychological pressures due to rapid market fluctuations, high uncertainty, and the need for split-second decisions. This paper explores the key psychological challenges faced by HFT practitioners, including stress, cognitive overload, emotional imbalance, and decision fatigue. The study analyses how these factors affect judgment accuracy, risk-taking behavior, and overall performance. It also highlights the importance of psychological resilience, effective stress-management strategies, and disciplined risk-management frameworks in minimizing human error. Understanding these psychological dimensions is crucial for developing healthier trading environments and enhancing the stability and efficiency of modern financial markets.